Decision-Making Methodologies for Reuse of Industrial Assets - J. Claver; A. García-Domínguez; M. A. Sebastián (Complexity, 2018)
When there is a social consensus that industrial assets are in fact heritage elements of cultural interest, their conservation and reuse must be considered with approaches that offer greater guarantees and that prevent their exposure to aggressive actions. In order for this to materialise, many aspects must be included in the decision-making process, from the characteristics of an asset and its surroundings, to the valuable aspects that distinguish it and that must be protected. This study aims to develop tools that guide the decision-making process regarding the most appropriate activity for each specific case study. Multicriteria Decision Support Techniques are evaluated as adequate support to create a proposal that fulfils these objectives. Furthermore, the Analytic Hierarchy Process is adapted to develop methodologies for assessing both the heritage value and the most compatible uses according to the characteristics of the asset. Subsequently, they are connected and such considerations regarding the heritage value of the asset are incorporated into the final decision. The tools developed are then applied to a case study to test their performance, assess their usefulness, and identify possible applications and future developments.